Jerarquización de los recursos urbanos y arquitectónicos del patrimonio industrial azucarero de la provincia de Camagüey en Cuba. - Herrera Pupo, Gerson (Museologia e Patrimônio, 2014)
For many years the sugar agro-industrial heritage has become part of the identity of the Cuban people. In this direction and with the imminent loss of authenticity and integrity, and the need to rescue the equity, we proceeded to the adequacy and implementation of a model that identified the main heritage resources linked to sugar production, potential and their hierarchization as a possible tourist attraction. The hierarchization process applied in the present province of Camagüey, define batey azucarero allowed with integrity and authentic characteristics as the largest unifying of heritage values. This enabled to demonstrate the potential that they possess as a tourist attraction, which is linked to the current processes of development of tourism industry in the study region. Keywords: Hierarchization of heritage resources. Heritage industrialist. Tourism potential.